THE EMERGENCE OF FOREIGN INTERVENTION AGAINST HUMAN RIGHTS VIOLATIONS IN ARMED CONFLICT IN A STATE - Mahfud SH (Jurnal IUS Kajian Hukum dan Keadilan, 2013)
The violation on the law of war and human right regulations may cause foreign (international) intervention  on every war violations, if violating country does not implement  the law enforcement for  the violating criminal. The international interventions to punish the violating actor (of the law of war and of human right) happening in a military conflict will occur  if the national court of the country is unwilling and unable to punish the prisoner of war . Key word ; The Violation of  the Law of War and Human Right, War Criminal